Stereotactic body radiation therapy for hepatocellular carcinoma: Practice patterns, dose selection and factors impacting survival - Jared R. Robbins; Ryan K. Schmid; Abdulrahman Y. Hammad; Thomas Clark Gamblin; Beth A. Erickson (Cancer Medicine)
Abstract Background Stereotactic body radiation therapy (SBRT) is an emerging option for unresectable hepatocellular carcinoma (HCC) without consensus regarding optimal dose schemas. This analysis identifies practice patterns and factors that influence dose selection and overall survival, with particular emphasis on dose and tumor size. Materials/Methods Query of the National Cancer Database (NCDB) identified patients with unresectable, nonmetastatic HCC who received SBRT from 2004 to 2013. Biological Effective Dose (BED) was calculated for each patient in order to uniformly analyze different fractionation regimens. Results A total of 456 patients met the inclusion criteria. The median BED was 100 Gy (22.5‐208.0), which corresponded to the most common dose fractionation (50 Gy in five fractions). Various factors influenced dose selection including tumor size (P < 0.001), tumor stage (P = 0.002), and facility case volume (<0.001). On multivariate analysis, low BED (<75 Gy, HR 2.537, P < 0.001; 75‐100 Gy, HR 1.986, P = 0.007), increasing tumor size (HR 1.067, P = 0.032), elevated AFP (HR 1.585, P = 0.019), stage 3 (HR 1.962, P < 0.001), low‐volume facilities (1‐5 cases HR 1.687, P = 0.006), and a longer time interval from diagnosis to SBRT (>2 to ≤4 months, HR 1.456, P = 0.048; >4 months, HR 2.192, P < 0.001) were associated with worse survival. Conclusion SBRT use is increasing for HCC, and multiple regimens are clinically employed. Although high BED was associated with improved outcomes, multiple factors contributed to the dose selection with favorable patients receiving higher doses. Continued efforts to enhance radiation planning and delivery may help improve utilization, safety, and efficacy.